2019
DOI: 10.1021/acsomega.8b03405
|View full text |Cite
|
Sign up to set email alerts
|

Development of Subair Technique for Combustibility Enhancement and NOx Reduction in a Pulverized Coal-Fired Boiler

Abstract: In this work, subair injection was proposed to improve the combustibility and NOx emission in a 500 MW tangentially fired coal boiler. The location of injection ports was determined based on the coal particle trajectory and its effect was investigated numerically. The flow rate of subair was set to 0, 5, and 10% of the total combustion air. The secondary air flow rate was decreased appropriately to ensure that the total quantity of combustion air remained constant. The over-fire air was not adjusted to retain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Extensive literature exists on the effects of boiler configuration or operating conditions on their performance, particularly NOx emissions at the pilot-scale and HELE utility boilers with one or more implemented low-NOx combustion technologies. Several numerical studies over the past decade have demonstrated the effectiveness of low-NOx combustion technologies, including low-NOx swirl burners, ,, the optimized ratio and position of OFA, LNCFSs, and air staging, , the sub air technique, HBC and OFA, the double-tangential-circle boiler, and advanced firing systems for down-fired boilers . Various parameters must be considered to evaluate their effects on low-NOx combustion in different boilers.…”
Section: Cfd Modeling Of Hele Coal Combustionmentioning
confidence: 99%
“…Extensive literature exists on the effects of boiler configuration or operating conditions on their performance, particularly NOx emissions at the pilot-scale and HELE utility boilers with one or more implemented low-NOx combustion technologies. Several numerical studies over the past decade have demonstrated the effectiveness of low-NOx combustion technologies, including low-NOx swirl burners, ,, the optimized ratio and position of OFA, LNCFSs, and air staging, , the sub air technique, HBC and OFA, the double-tangential-circle boiler, and advanced firing systems for down-fired boilers . Various parameters must be considered to evaluate their effects on low-NOx combustion in different boilers.…”
Section: Cfd Modeling Of Hele Coal Combustionmentioning
confidence: 99%
“…In boilers that operate at non-high temperatures, fuel NOx accounts for most of the boiler emissions (fuel NOx accounts for 95% in the fluidized bed, and the corners are generally rounded about 75%). Volatile NOx accounts for 60%-80% of the final NOx emission of the boiler, while coke NOx only accounts for a small part [5][6][7][8].The main purpose of the low-nitrogen burner modification is to control the amount of NOx generated by the fuel type and the thermal type NOx. The main method is to control the airfuel ratio in the local area of the boiler and the maximum temperature of combustion in the furnace.Domestic low-nitrogen burners reduce NOx by realizing pulverized coal concentration separation, air graded combustion, and large burn-out air rate [9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly used NO x control technologies are selective non‐catalytic reduction (SNCR) and selective catalytic reduction (SCR). The latter has become an important process to control NO x emission in coal‐fired power plants and automobiles [4–6] . In addition to NO x , the carbon monoxide (CO) emitted by automobiles at the same time will also cause great damage to the environment [7,8] .…”
Section: Introductionmentioning
confidence: 99%